The reality of the curriculum of teaching the recorder for the second year students at the Institute of Teachers' Preparation in Damascus and preparing a proposed vision (Damascus University Journal of educational and Psychologyical sciences, 2024)
The study aimed to prepare a suggested vision for the recorder machine curriculum. In this study, the researcher adopted the descriptive analytical method, and the research sample represented all members of the original community of second-year students. Thus, the research sample consisted of (50) male and female second-year students at the Institute for Preparing Teachers of Music Education in Damascus, and the research tool was the questionnaire. The study concluded  To a set of results, the most important of which was that second-year students believe that the curriculum for teaching the recorder instrument is inappropriate and does not comply with modern curricula for this instrument, as the average opinion of the sample members was 2.51. In addition,this curriculum is not appropriate for the preparation of music education teachers, and does not take into account the diversity of the social classes of learners and the culture possessed by teachers and learners of the basic education stage. In addition to some positive aspects of the curriculum, it takes into account modern and traditional oriental music and includes comprehensive objectives for all levels of learning and appropriate modern teaching and evaluation methods. The results also showed that there were no statistically significant differences between the average scores of the research sample members regarding the reality of the curriculum for teaching the recorder to second-year students at the Teacher Preparation Institute in Damascus according to the gender variable. A suggestion vision was also developed to develop the curriculum based on the results of the approved curriculum level and the student’s level in playing the recorder.
Keywords: Curriculum For Teaching The Recorder Instrument; Institute For Preparing Music Education Teachers; Suggested Vision